Minimal leptoquark explanation for the RD(∗), RK and (g−2)μ anomalies - Bauer, Martin; Neubert, Matthias (Physical review letters, 2016)
We show that by adding a single new scalar particle to the standard model, a TeV-scale leptoquark with the quantum numbers of a right-handed down quark, one can explain in a natural way three of the most striking anomalies of particle physics: the violation of lepton universality in ¯B→¯Kℓ+ℓ− decays, the enhanced ¯B→D(*)τ¯ν decay rates, and the anomalous magnetic moment of the muon. Constraints from other precision measurements in the flavor sector can be satisfied without fine-tuning. Our model predicts enhanced ¯B→¯K(*)ν¯ν decay rates and a new-physics contribution to Bs−¯Bs mixing close to the current central fit value.